SENSOR-SENSOR PEMANTAU MENGGUNAKAN ARDUINO UNO DAN ESP8266 DIUNGGAH KE THINGSPEAK SERVER UNTUK PENGUKURAN GASDI TEMPAT PEMBUANGAN AKHIR MANGGAR BALIKPAPAN - charles pangaribuan; agus beny imron (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2018)
Abstract—Oil and gas industri is one of very development sector in technology. The data acquisition system or telemetry with remote monitoring and storage are one of them. Today, this technology can be applicated into society to be usefull and give more advantages. By using an open data platform for Internet of Things (IoT), it is very possible. -Final landfil has produced many gasses such as methane and carbondiokside, especially methane gas which is produced by deterioration of organic waste. These emit gasses are one global warming root caused, we call it green house effect gasses. The gas concentrations is hard to be measured without a device help, it is safe and prefered. -On this final project the we build build a prototype that contain Arduino Uno, ESP826 Wi-Fi module and Sensors. It detects reading for Methane (CH4) , Carbon Dioxide (CO2), Temperature and Humidity. All reading data for gasess, temperature and humidity then send throught Wi-Fi internet be uploaded into www.thingspeak.com,using internet browser we can view the reading graph from ThingSpeak, anyone who has internet acces can be seen all the dataremotel